Catalytic Degradation and Antibacterial Activity of Cinnamon-Mediated Green Synthesized Silver Nanoparticles Loaded on Alginate Beads - Alshameri, Dhoha; Al-Hannan, Fatima; Henari, Fryad; Deen, G. Roshan (Journal of Research Updates in Polymer Science, 2024)
Alginate-silver nanocomposites in the form of spherical beads were prepared using a green approach by using the aqueous extract of cinnamon bark. The nanocomposites were fabricated by a three-step process involving gelation by ionotropic crosslinking, adsorption, and in situ chemical reduction in solution. The rich phytochemicals of the cinnamon bark extract played a dual role as reducing and stabilizing agent in the synthesis of silver nanoparticles of average size of 16 nm. The presence of silver nanoparticles in the nanocomposite was studied using UV-Vis absorption spectroscopy, electron microscopy and energy dispersive x-ray spectroscopy. The morphology of the nanocomposite beads was dense and compact with random distribution of silver nanoclusters. The catalytic property of the nanocomposite beads was evaluated for the degradation of Congo-red dye in the presence of sodium borohydride. The degradation followed pseudo-first order kinetics with a rate constant of 0.012 min-1 at 23 °C. The activation energy for the degradation process was 27.57 ± 1.5 kJ mol-1. The thermodynamic parameters such as the enthalpy and entropy changes were evaluated using the Eyring equation and were determined to be 0.123 ± 0.05 kJ mol-1 and -197.25 ± 2 J mol-1 K-1, respectively. The nanocomposite exhibited antibacterial properties against the two strains of bacteria, Escherichia coli and Staphylococcus aureus.